Anemic Retinopathy as a Presenting Feature of Severe Dimorphic Nutritional Anemia in a Young Male Patient after Crash Dieting - Parul Jain; Abhilasha Sanoria (Indian Journal of Medical Specialities)
We report the case of a 31-year-old male patient who presented for a routine ophthalmological examination. Evaluation revealed the presence of bilateral flame-shaped hemorrhages and Roth's spots. Hematological evaluation revealed the presence of severe iron deficiency anemia with megaloblastic anemia. This case documents the occurrence of anemic retinopathy in dimorphic nutritional anemia after crash dieting (severe calorie restriction).